Status of modern mirror studies in Novosibirsk - Kruglyakov, E.P.; Ivanov, A.A.; Koidan, V.S. (Вопросы атомной науки и техники, 2005)
Mirrors have a number of advantages in comparison with the closed magnetic systems like tokamak, stellarator, etc. In principle, mirrors are very attractive from the engineering point of view, if the plasma confined in axisymmetric magnetic systems would be MHD stable. At present, the MHD stabile confinement has already been demonstrated for all axisymmetric traps designed in Novosibirsk for the value of β value as high as 0.4. Some important results were obtained recently in the GOL- 3and GDT experiments. In the paper, the status of two mirror traps in Novosibirsk is presented and description of the main experimentsis given. Відкриті магнітні пастки мають ряд переваг у порівнянні з замкнутими магнітними системами, подібними токамаку, стелларатору і т.д. У принципі, відкриті системи досить привабливі з інженерної точки зору, якщо плазма утримується в осесиметричній магнітній конфігурації, залишаючись МГД стійкої. В даний час МГД стійке утримання вже продемонстроване для осесиметричних пасток, досліджуваних у Новосибірську, аж до величини β=0.4. Важливі результати отримані недавно на установці ГОЛ-3 і в експериментах з газодинамічною пасткою ГДЛ. У даній роботі представлений стан робіт на двох магнітних пастках у Новосибірську і приведені результати основних експериментів. Открытые магнитные ловушки имеют ряд преимуществ по сравнению с замкнутыми магнитными системами, подобными токамаку, стелларатору и т.д. В принципе, открытые системы весьма Problems of Atomic Science and Technology. 2005. № 1. Series: Plasma Physics (10). P. 7-11 привлекательны с инженерной точки зрения, если плазма удерживается в осесимметричной магнитной конфигурации, оставаясь МГД устойчивой. В настоящее время МГД устойчивое удержание уже продемонстрировано для осесимметричных ловушек, исследуемых в Новосибирске, вплоть до величины β =0.4. Важные результаты получены недавно на установке ГОЛ-3 и в экспериментах с газодинамической ловушкой ГДЛ. В данной работе представлено состояние работ на двух магнитных ловушках в Новосибирске и приведены результаты основных экспериментов.